Lift and shift: The effect of fundraising interventions in charity space and time - Kimberly A. Scharf; Sarah Smith; Mark Ottoni Wilhelm (Institute for Fiscal Studies (IFS), 2017)
Fundraising interventions may lift donations and/or shift their composition and timing, making it important to study their effect across charity space and time. We find that major fundraising appeals lift total donations, but surprisingly shift donations to other charities across time. To explain this, we develop a two-period model with two sources of warm glow that relates donation responses to underlying preference parameters. A dynamic framework, combined with rich data, provides opportunities to identify substitutability/complementarity in warm glow. The observed pattern is possible only if the two sources of warm glow are substitutes and warm glow is intertemporally substitutable.
Keywords: H41; D12; D64; 330; Warm glow; donations; substitution; intertemporal substitution; Fundraising; Wirkungsanalyse; Altruismus; Philanthropie; Intertemporale Entscheidung; Schätzung; Großbritannien